2016
DOI: 10.4103/0971-9784.191580
|View full text |Cite
|
Sign up to set email alerts
|

Variations of transesophageal echocardiography practices in India: A survey by Indian College of Cardiac Anaesthesia

Abstract: Context:Use of perioperative transesophageal echocardiography (TEE) has expanded in India. Despite attempts to standardize the practice of TEE in cardiac surgical procedures, variation in practice and application exists. This is the first online survey by Indian College of Cardiac Anaesthesia, research and academic wing of the Indian Association of Cardiovascular Thoracic Anaesthesiologists (IACTA).Aims:We hypothesized that variations in practice of intraoperative TEE exist among centers and this survey aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…10 TEE has been widely used as a monitoring tool for decision making and surgical planning in cardiac surgery. 11 Though considered to be relatively safe, there is an incidence of 1.4% complication related to TEE including dysphagia, vocal cord and laryngeal injury and esophageal perforation. 12 Besides this as TEE probe is just adjacent to trachea, the increase in cuff pressure can lead to post-operative sore throat, subglottic edema with stridor or tracheal stenosis in cardiac surgical cases where TEE probe stays in situ for prolong period and there is also periods of decreased perfusion pressure in hypotensive phages.…”
Section: Discussionmentioning
confidence: 99%
“…10 TEE has been widely used as a monitoring tool for decision making and surgical planning in cardiac surgery. 11 Though considered to be relatively safe, there is an incidence of 1.4% complication related to TEE including dysphagia, vocal cord and laryngeal injury and esophageal perforation. 12 Besides this as TEE probe is just adjacent to trachea, the increase in cuff pressure can lead to post-operative sore throat, subglottic edema with stridor or tracheal stenosis in cardiac surgical cases where TEE probe stays in situ for prolong period and there is also periods of decreased perfusion pressure in hypotensive phages.…”
Section: Discussionmentioning
confidence: 99%
“…TEE has evolved as a major monitoring and diagnostic tool during cardiac surgery in the last few decades. According to a recent survey,[ 19 ] new findings are considered in decision-making, and surgical plan is altered in many cases from TEE findings. TEE is considered as a relatively safe procedure, still overall incidence of TEE complications after cardiac surgery can be as much as 1.4% patients including dysphagia, vocal cord and laryngeal injury, dysphonia, esophageal, and gastric lacerations.…”
Section: Discussionmentioning
confidence: 99%
“…TEE plays important role in monitoring and preventing complications related to CPB. Various uses of TEE are to assist cannulation and feasibility, examining the aorta for atheromas, early identification of iatrogenic complications like aortic dissection, or assist de-airing after releasing the aortic cross-clamp, etc., Previously, in an IACTA survey,[21] it was reported that 76% IACTA members have access to TEE probe and echo machine, which is dedicated to cardiac operation theaters. In the present survey, it was demonstrated that 51% of centers use TEE routinely, 38% of centers use them at least sometimes.…”
Section: Discussionmentioning
confidence: 99%